SYSTEM‐AWARE CYBER SECURITY: A SYSTEMS ENGINEERING APPROACH FOR ENHANCING CYBER SECURITY. Issue 2 (July 2016) - Horowitz, Barry M.; Lucero, D. Scott
ABSTRACT: This article highlights the importance of concurrently addressing process, people, and technology factors when conducting research related to new systems engineering concepts. In particular, an ongoing US Department of Defense‐sponsored, University of Virginia‐led cyber security research project is used as an example of how concurrent research activities provide value earlier in the technology design phase than otherwise would have occurred. The example project focuses on adding a new layer of protection for computer‐controlled physical systems. Through concurrent efforts, the research team developed a better a protection approach, resulting in better prospects for transition into use.